A LOOK AT THE PERSONAL ARCHIVE OF V.A. SHISHKIN (Scientific journal of the Fergana State University, 2024)
In this article, the Museum, which preserves the State Fund of the East, tells about its personal archive of V.A.Shishkin. The museum claims that the diary entries of the scientist, in which field research materials were recorded, were provided by his children, and the diaries summarize information about the masas of Central Asian archaeology and the archeology of the Bukhara oasis. It is also recorded that the scientist published monographs, brochures and collections as a result of his archaeological expeditions.